1986
DOI: 10.1136/gut.27.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Transit of pharmaceutical dosage forms through the small intestine.

Abstract: SUMMARY The gastrointestinal transit of pharmaceutical dosage forms has been measured in 201 studies in normal subjects using gamma scintigraphy. Solutions, small pellets, and single units (matrix tablets and osmotic pumps) were administered with different amounts of food in the stomach, ranging from fasted state to heavy breakfast. Gastric emptying was hiffected by the nature of the dosage form and the presence of food in the stomach. Solutions and pellets were emptied even when the stomach was in the digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
319
3
9

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 776 publications
(362 citation statements)
references
References 16 publications
(6 reference statements)
24
319
3
9
Order By: Relevance
“…Despite the reasonably constant small intestinal transit time (cfr. supra: Scintigraphy), the food or drug matrix spends a considerable time at the ileocecal junction, which functions mechanistically as a valve allowing fecal material to become more concentrated before transfer to the colon (Davis et al, 1986). For time-dependent colonic drug delivery systems, which will release drug after a predetermined lag time, movement through this junction can be a significant variable (Jose et al, 2009; a b c Kinget et al, 1998;Pišlar et al, 2015;Wilson, 2010).…”
mentioning
confidence: 99%
“…Despite the reasonably constant small intestinal transit time (cfr. supra: Scintigraphy), the food or drug matrix spends a considerable time at the ileocecal junction, which functions mechanistically as a valve allowing fecal material to become more concentrated before transfer to the colon (Davis et al, 1986). For time-dependent colonic drug delivery systems, which will release drug after a predetermined lag time, movement through this junction can be a significant variable (Jose et al, 2009; a b c Kinget et al, 1998;Pišlar et al, 2015;Wilson, 2010).…”
mentioning
confidence: 99%
“…Food has been shown (Nyberg, 1984) to reduce the bioavailability of terbutaline and as the evening dose was taken only 2 h after intake of supper, when the stomach still should not be quite empty (Davis et al, 1986), this could influence the extent of absorption especially with a sustained-release preparation. A decreased gut motility, during the night, could also reduce the absorption of terbutaline.…”
Section: Terbutalinementioning
confidence: 99%
“…In addition, results of the kinetic studies shown that maximum binding to bile acids achieved in 15-30 min. When taken tablets with a meal, it takes much longer than 30 min to pass through the intestine [14]. Therefore, the tablets perform maximum binding pass through the intestine.…”
Section: Mean Test/mean Reference (T/r) Of Twelve Determination Resultsmentioning
confidence: 99%